Autour de la figure de Marie Stuart - Le Baillif, Anne-Marie (Nordlit, 2012)
The Sixteenth century constitutes an inspiration for writers of the nineteenth century. My paper is based on two works: Jean de Virey’s tragédie: Jeanne d’Arques published in 1600; Le quadrille de la duchesse de Berry which took place in 1829. In both the life of Marie, Queen of Scots, is given a political meaning: she was a woman who made herself conspicuous and consequently became a symbol of decadent power.